Performance analysis and transient simulation of a vapor compression cooling system integrated with phase change material as thermal energy storage for electric peak load shaving. (March 2021) - riahi, Alireza; Mosleh, Hassan Jafari; Kavian, Soheil; Shafii, Mohammad Behshad
Highlights: A vapor-compression cooling system utilizing PCM as cooling storage is presented. The main objective is to shift the electricity consumption peak. lower power consumption during the peak load hours is observed. A 47% reduction in peak load on the hottest day of the year is observed for the PCM volume of 154 liters. For a minimal drop in COP, the compressor power experiences a significant drop at peak load hours. The economic analysis showed that depending on the electricity consumption price, the integration of PCM storage can be hugely profitable in terms of economic parameters as it can lead to peak load shavings of up to 69%. Abstract: A vapor-compression cooling system utilizing PCM is studied whereby the electricity consumption peak load is shifted. More specifically, the dynamic performance of the cooling system with and without PCM is evaluated and is presented with details on the hottest day of the year in Tehran, Iran. The proposed system uses the cooling energy to freeze or "discharge" the PCM during nighttime when the cooling load is minimally needed and uses the stored cooling energy during the peak load hours by melting or "charging" the PCM. This leads to better performance during the peak load hours when higher cooling loads are required. Oleic acid was chosen as PCM. The simulation was performed in EES software. The system performance was investigated by evaluating several parameters such as coefficient of performance, compressor power consumption, accessible cooling load, melting fraction of PCM, evaporator outlet temperature, compressor outlet temperature, and saturation temperature of the condenser. The effect of different volumes of PCM and different daily temperatures was also investigated. Finally, the economic analysis was performed for different conditions. The results showed that PCM increases the accessible cooling load and decreases the electricity consumption during the peak load hours. For the PCM volume of 154 L, the daily accessible cooling energy, daily energy consumption, and electricity peak load have a 2.9%, 0.9%, and 47% reduction on the hottest day of the year, respectively. Increasing the PCM volume leads to a lower PCM melting fraction but a higher melting time during the peak load hours. For an increase from 38 L to 309 L in PCM volume, the melting time increases by 35%. Also, the daily accessible cooling load and the energy consumption decrease by 6.9% and 4.5%, respectively which leads to a 2.7% reduction in the COP. However, for the same change in the PCM volume, peak shaving increases from 12.7% to 68.7%. The economic analysis showed that depending on the electricity consumption price, the integration of PCM storage can be hugely profitable in terms of economic parameters as it can lead to peak shavings of up to 69%.